2022
DOI: 10.35946/arcr.v42.1.08
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Alcohol and Marijuana Use Among Young Adults: A Scoping Review of Prevalence, Patterns, Psychosocial Correlates, and Consequences

Abstract: BACKGROUND Alcohol and marijuana are commonly used by young adults, and use of both substances, particularly at the same time, is prevalent among this population. Understanding the prevalence, patterns, correlates, and consequences of simultaneous alcohol and marijuana (SAM) use is important to inform interventions. However, this literature is complicated by myriad terms used to describe SAM use, including use with overlapping effects and same-day co-use. OBJECTIVES Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 97 publications
3
53
0
Order By: Relevance
“…Young adults are a high-risk group for alcohol and cannabis use; among a national United States sample of young adults, the majority reported alcohol use, and nearly half reported cannabis use in the past 12 months (Patrick et al, 2022). Further, many young adults engage in simultaneous use (using both alcohol and cannabis at the same time, so that effects overlap) and same-day co-use (using alcohol and cannabis on the same day, but not necessarily at the same time; Lee et al, 2022). Research has identified substance use motives as one of the most proximal predictors of substance use behaviors.…”
Section: Social Anxiety Coping Motivesmentioning
confidence: 99%
“…Young adults are a high-risk group for alcohol and cannabis use; among a national United States sample of young adults, the majority reported alcohol use, and nearly half reported cannabis use in the past 12 months (Patrick et al, 2022). Further, many young adults engage in simultaneous use (using both alcohol and cannabis at the same time, so that effects overlap) and same-day co-use (using alcohol and cannabis on the same day, but not necessarily at the same time; Lee et al, 2022). Research has identified substance use motives as one of the most proximal predictors of substance use behaviors.…”
Section: Social Anxiety Coping Motivesmentioning
confidence: 99%
“…Past daily studies comparing alcohol use and intoxication levels across alcoholonly and co-use days show mixed findings (Lee et al, 2022). To my knowledge, the present study is the first to show that students may drink more heavily when using alcohol first on SAM use days, helping to explain past discrepancies in alcohol use across days.…”
Section: Alcohol Use Was Greater On Sam Use Days Than On Alcohol-only...supporting
confidence: 44%
“…Interest in understanding the risks conferred by patterns of simultaneous use has been increasing (Lee et al, 2022) alongside the greater incidence of co-use in young adults (McCabe et al, 2021). Most of the research in the human literature focuses on acute effects of simultaneous use, and specifically on the immediate consequences that are self-reported by users of these drugs (Lee et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Interest in understanding the risks conferred by patterns of simultaneous use has been increasing (Lee et al, 2022) alongside the greater incidence of co-use in young adults (McCabe et al, 2021). Most of the research in the human literature focuses on acute effects of simultaneous use, and specifically on the immediate consequences that are self-reported by users of these drugs (Lee et al, 2022). When longitudinal studies are conducted, they most frequently compare “heavy” users of one or both drugs to non-using controls, and even then the criteria for heavy frequency of use is inconsistent, making it difficult to paint a comprehensive picture (Karoly et al, 2020).…”
Section: Discussionmentioning
confidence: 99%